Indikator Kinerja dan Peran Stakeholder dalam Pengelolaan Daerah Aliran Sungai (DAS) Lisu - Yulsan Demma Semu; Usman Arsyad; Anwar Umar (Fakultas Kehutanan, Universitas Hasanuddin, 2018)
Various community activities that have occurred in the Lisu Watershed have seemed irregular and unregulated. This can be seen in the management of the Lisu watershed, which has not been used thoroughly from policy, implementation to evaluation and monitoring in the management of the Lisu watershed. The emergence of various problems and conflicts between various interests in its management. So the purpose of this study is how to analyze collaboration and stakeholder synergy in natural resource management in the Lisu Watershed. This research was conducted with descriptive exploratory analysis method on the activities of stakeholders who will collaborate in the management of the Lisu watershed, and how to identify performance indicators. The results obtained in this study are the overlapping functions, duties and responsibilities and authority in the management of the Lisu watershed. Related stakeholders have not been based on effectiveness, namely the goals and objectives in improving the quality of the Lisu watershed, causing a conflict of interest and lack of coordination. Another obstacle faced by stakeholders in collaborating and synergy is the disagreement of some stakeholders in integrating watershed management whose management is from upstream, middle and downstream of the Lisu watershed. The recovery policy in the Lisu Watershed is needed in realizing and building integrated watershed management patterns in collaboration and stakeholder synergy. As well as the need for a change of management paradigm as well as institutional strengthening in the management of the Lisu Watershed.